Meis1 is required for the maintenance of postnatal thymic epithelial cells. - Takehiro Hirayama; Yusuke Asano; Hajime Iida; Takeshi Watanabe; Takuro Nakamura; Ryo Goitsuka (PLoS ONE)
Most epithelial tissues retain stem/progenitor cells to maintain homeostasis of the adult tissues; however, the existence of a thymic epithelial cell (TEC) progenitor capable of maintaining homeostasis of the postnatal thymus remains unclear. Here, we show that a cell population expressing high levels of Meis1, a homeodomain transcription factor, is enriched in TECs with an immature cellular phenotype. These TECs selectively express genes involved in embryonic thymic organogenesis and epithelial stem cell maintenance, and also have the potential to proliferate and differentiate into mature TEC populations. Furthermore, postnatal inactivation of Meis1 in TECs caused disorganization of the thymic architecture, which ultimately leads to premature disappearance of the thymus. There was an age-associated reduction in the proportion of the TEC population expressing high levels of Meis1, which may also be related to thymic involution. These findings indicate that Meis1 is potentially involved in the maintenance of postnatal TECs with progenitor activity that is required for homeostasis of the postnatal thymus.